Siri’ Killing dalam Masyarakat Bugis-Makassar: Konstruksi, Pola Pembunuhan, dan Respons Hukum Pidana - Zul Khaidir Kadir (PT. PENERBIT TIGA MUTIARA, 2026)
This study examines the phenomenon of siri’ killing in the Bugis-Makassar community, which has received limited attention in global discussions on honor-based killings. The background of this research is rooted in the strong value of siri’ as a system of collective honor that not only regulates social behavior but also has the potential to generate violence as a means of restoring dignity. The research problem focuses on how the construction of siri’ shapes collective honor, how patterns of honor-motivated killings occur, and how Indonesian criminal law responds to this phenomenon without legitimizing violence. This study employs a normative legal method with statutory, case, and conceptual approaches to analyze the relationship between legal norms and cultural values. The findings indicate that siri’ is understood as a collective family identity that significantly influences individual behavior, with women becoming the most vulnerable group due to the unequal distribution of moral burden. Patterns of siri’ killing are generally associated with control over sexuality and marriage and are driven by social pressure and collective moral legitimacy. The response of criminal law tends to be ambivalent, as cultural motives are not justified but are often considered as background factors. The conclusion emphasizes that siri’ killing is a complex phenomenon that cannot be understood merely as a criminal act, but rather as the result of interactions among culture, gender, and law. The novelty of this study lies in the integration of cultural, criminal law, and gender perspectives in explaining siri’ killing as a localized form of honor killing with distinctive characteristics in Indonesia.